Criteria for cure of acromegaly: a consensus statement. - Giustina, A; Barkan, A; Casanueva, F; Cavagnini, F; Frohman, L; Ho, K; Veldhuis, J; Wass, J; Von Werder, K; Melmed, S (2000)
In February 1999, a workshop was held in Cortina, Italy to develop a consensus defining the criteria for cure of acromegaly. The workshop was sponsored by the University of Brescia and hosted by the Italian Society of Endocrinology. Invited international participants included endocrinologists, neurosurgeons, and radiotherapists skilled in the management of acromegaly. This statement summarizes the consensus achieved in these discussions.